On spline methods of approximation under L-fuzzy information - Asmuss, Svetlana; Sostak, Alexander (2011 IEEE International Conference on Fuzzy Systems (FUZZ-IEEE 2011), 2011)
This work is closely related to our previous papers on algorithms of approximation under L-fuzzy information. In the classical theory of approximation central algorithms were worked out on the basis of usual, that is crisp splines. We describe central methods for solution of linear problems with balanced L-fuzzy information and develop the concept of L-fuzzy splines.